Tofacitinib for child-onset systemic lupus erythematosus - Hou, Ling; Zhou, Peng; Zhao, Chengguang; Wang, Xiuli; Du, Yue (Frontiers in Immunology, 2024)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that can cause diverse clinical manifestations in multiple organ systems. Child-onset SLE (cSLE) is associated with significantly higher morbidity and mortality than adult-onset SLE. The traditional treatments for SLE (glucocorticoids, antimalarials, conventional and biological disease-modifying antirheumatic drugs) often have significant adverse effects and may not fully control disease activity. Tofacitinib is an oral Janus kinase (JAK) inhibitor that inhibits the JAK-STAT pathway and has the potential to reduce SLE severity. Methods: cSLE patients who received tofacitinib and had at least one follow-up visit were retrospectively examined. Case histories, laboratory test results, and treatment regimens were analyzed at disease onset, initiation of tofacitinib treatment, and 1, 3, 6, 9, 12, 18, and 24 months after starting tofacitinib. Results: We examined 9 patients with refractory cSLE. All patients were female and the average age at diagnosis was 10.67 years. At initiation of tofacitinib, the average age was 13.28 years and the average disease duration was 2.62 years. Four patients experienced alleviation of symptoms and reduced their daily prednisone dosages; one of them also discontinued cyclosporine A and two of them also discontinued belimumab. The other 5 patients experienced no apparent benefit. Conclusion: Tofacitinib may provide clinical benefits for some patients with refractory cSLE, and can also allow reduction in the glucocorticoid dosage. Tofacitinib has the potential as an adjunctive treatment for some patients with cSLE.